11.9k views
23 votes
How do i answer this question?

How do i answer this question?-example-1
User Umki
by
4.5k points

2 Answers

7 votes
f(x) = 3x-1
y = 3x-1
——
x = 3y - 1
y = (x+1)/3
f^-1(x) = (x+1)/3
____
f^-1(59) = (59+1)/3 = 60/3 = 20
User Abed Putra
by
4.6k points
9 votes

Answer:


f^(-1) (59) = 20

Explanation:


f^(-1) (x) is the inverse of f(x)

to find the inverse function, let f(x) = y and rearrange to make x the subject.

y = 3x - 1 ( add 1 to both sides )

y + 1 = 3x ( divide both sides by 3 )


(y+1)/(3) = x

change y back into terms of x with x =
f^(-1) (x) , then


f^(-1) (x) =
(x+1)/(3) , then


f^(-1) (59) =
(59+1)/(3) =
(60)/(3) = 20

User Milan Nankov
by
4.8k points